Determining Variation in Women's Labor Force Participation in a Fragile Region of Sub-Saharan Africa Using Cochran's Q Statistic - Abegunde, Albert Ayorinde; Mobolaji, Jacob Wale; Olayiwola, Lasun Mykail; Akinyemi, Akanni; Alade, Adeyemi Adewale; Fika, Ore; Ezike, Ifeoma Betty (Promoting Statistical Practice and Collaboration in Developing Countries, 2022)
Cochran's Q statistic is peculiar in analyzing data collected in three repeated forms. Its application is tested here to establish variation in women's labor force participation (LFP) before, during, and after conflicts in Southwestern Nigeria where dual discrete communities from each of the four different fragile areas engaged in intercommunal crises. The study, focusing on women (n = 181) living in these conflict-affected communities observed that most of them were mid-age poor rural-based married Christians who lost spouses to conflicts and had below tertiary education. The level of their LFP before (70.2%) reduced during (66.7%) and rose after (75.6%) the conflicts significantly among unmarried women (Cochran's Q = 11.700; p < 0.05) and higher among those in the rural settlements but decreased with increasing level of education. Women that earned low monthly income (below N18000 or $79.00) after conflicts fairly reduced (68.4%) compared to the period before (82.7%), although without significant improvement among their high-income counterparts. Conclusion on the Cochran's Q test application here showed that improved employment among the poor women after conflicts raised hope on gender's role and challenged African policymakers to support women for better gender contribution to economic peace-building of post-conflict communities.